Концепт «чужина» в українській народній пісні - Іовхімчук, Наталія Володимирівна; Iovkhimchuk, Nataliia V. (Національний університет "Острозька академія", 2015)
У роботі розглянуто семантику слова-концепту чужина в українських народних піснях. Саме ця лексема стала об’єктом аналізу цієї статті. До лексико-семантичного поля чужина визначено типові дієслова, синонімічні вислови до лексеми. Український пісенний фольклор фіксує також зменшувальні форми слова-концепту чужина. This article examines the semantics of the word-concept in a foreign land Ukrainian folk songs. It is this token become the object of analysis of this article. In Ukrainian folk songs images of characters - is a special way to reflection of reality, which reflect the different stages of the categories of folk perception of space. To lexical-semantic field of common foreign land defined verb, synonymous expressions to the token. Ukrainian folk songs also fixes diminutive form of the word-concept foreign land.
The concept «of foreign land» in ukrainian folk song
Keywords: семантика; чужина; далекий простір; далека земля; чужа сторона; чужа земля; чужий край; semantics; foreign land; far space far land; alien party; alien land; alien land